Impact of Reticulated Platelets on the Antiplatelet Effect of the Intravenous P2Y12-Receptor Inhibitor Cangrelor - Stratz, Christian; Nührenberg, Thomas; Valina, Christian M.; Löffelhardt, Nikolaus; Mashayekhi, Kambis; Ferenc, Miroslaw; Trenk, Dietmar; Neumann, Franz-Josef; Hochholzer, Willibald (Thrombosis and Haemostasis, 2018)
Background Reticulated platelets are associated with impaired antiplatelet response to irreversibly acting P2Y12-receptor inhibitors. However, the impact of reticluated platelets (RP) on the reversibly acting injectable P2Y12-receptor inhibitor cangrelor is unknown. Thus, this study sought to investigate the influence of RP on cangrelor and transitioning strategies to oral P2Y12-receptor inhibitors.Methods This study randomized 110 patients undergoing elective percutaneous coronary intervention with use of cangrelor to different oral transitioning strategies loading with prasugrel 60 mg or ticagrelor 180 mg at the start of cangrelor (n = 45 each) or loading with clopidogrel 600 mg after discontinuation of cangrelor (n = 20). ADP-induced platelet reactivity was assessed by impedance aggregometry. Reticulated platelets were analysed by an automated whole blood flow cytometry and described as immature platelet count.Results There was no correlation of reticulated platelets and ADP-induced platelet reactivity in patients under treatment with cangrelor (r = 0.06, p = 0.47). This finding was consistent in all three transitioning strategies. On day 1 following treatment with cangrelor, the correlation of reticulated platelets and platelet reactivity was detectable again in patients receiving thienopyridines but not ticagrelor (all patients r = 0.37, p < 0.001; clopidogrel: r = 0.59, p = 0.01; prasugrel: r = 0.47, p < 0.001; ticagrelor r = 0.22, p = 0.13).Conclusion Platelet inhibition is not influenced by levels of reticulated platelets during infusion of cangrelor independent of oral P2Y12-receptor inhibitor transitioning strategy. These findings underline the potency of cangrelor as immediate and reversibly acting P2Y12-receptor inhibitor.
Keywords: immature platelets; reticulated platelets; cangrelor; prasugrel; ticagrelor; platelet reactivity